Professional self-determination of personality and strategies of student youth - I. M. Zavelskaya (Publishing House of the State University of Management, 2019)
The actual problem of professional self-determination and professional strategies of student youth has been examined. Various approaches to the study of youth selfdetermination have been considered. Typologies of the professional strategies have been adduced. The division of the professional strategies into active and passive helps to describe more accurately the professional self-determination of the individual. The study of this issue will help in the formation and implementation of a competent social policy based on the interest of the younger generation.